The effects of reed density, surface and management on the probability of cuckoo (Cuculus canorus) parasitism on great reed warbler (Acrocephalus arundinaceus) nests. Issue 1 (2nd January 2019) - Mérő, Thomas O.; Žuljević, Antun
Abstract : While some previous investigations have been made into the effects of vegetation structure on the probability of brood parasitism in reed passerines, the effects of vegetation management remain unclear. Furthermore, we possess little information on how vegetation density influences the probability of brood parasitism in wide-surfaced reed-beds. The aim of this study was to test how vegetation density and reed management by burning influence the probability of cuckoo ( Cuculus canorus ) brood parasitism in great reed warbler ( Acrocephalus arundinaceus ) nests in a wide-surfaced reed-bed with pure reed stands. We found that the probability of parasitism was highest in nests constructed in low reed density, with low annual variation of reed density and low annual variation of nest height. Reed management had no effect on the probability of parasitism. Our results suggest that, in wide-surfaced reed-beds with pure reed stands, nests in sparser reed are more exposed to brood parasitism than those concealed in dense reed. Furthermore, low spatio-temporal variation in reed density and nest height benefit brood parasitism, as it provides a relatively constant number of host nests in a similar spatial distribution in the reed-bed from year to year. Vegetation structure was suggested to have an important role in adaptation of hosts' defence against brood parasites.